The diary of a young girl : the definitive edition - Frank, Anne, 1929-1945.; Frank, Otto, 1889-1980.; Pressler, Mirjam (New York : Doubleday, 1995)
An adolescent Jewish girl chronicles her experiences over the years she and several others hid from the Nazis in a secret apartment before being discovered and sent to concentration camps. Includes entries previously omitted.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), May 1997.
Booklist, May 1998.
Books for the Teen Age (NYPL), May 2004.
Keywords: Frank, Anne, -- 1929-1945 -- Diaries; Frank, Anne, -- 1929-1945 -- Diaries; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives; Jews -- Persecutions -- Netherlands -- Amsterdam; Jews -- Netherlands -- Amsterdam -- Diaries; Holocaust, 1939-1945 -- Personal narratives; Jews -- Amsterdam (Netherlands) -- Diaries; Jews -- Amsterdam (Netherlands) -- Persecutions; Amsterdam (Netherlands) -- Ethnic relations; Amsterdam (Netherlands) -- Ethnic relations